Upaya Rebranding Produk Property Pada Perumahan dalam Meningkatkan Kredibilitas Pembeli Pada PT. Cendana Indo Pratama - Cahyaningtiyas, Ayu; Wahab, Abd. Azis; Fajri, Ahmad (Jurnal Informatika Ekonomi Bisnis, 2023)
Cendana Indo Pratama is a company engaged in the General Contractor field, among the business units developed by PT. Cendana Indo Pratama, one of which is in the property sector which is currently being built, namely the Bimura Residence housing in the Paiton area, as we know many residential businesses have been built, especially in the Paiton area, East Java. In early 2022 PT. Cendana Indo Pratama is rebranding the Bimura Residence housing. The purpose of this research is to describe the basic subsidy rebranding efforts at Bimura Residence, and subsidy basic rebranding in increasing buyer credibility and what are the supporting factors in increasing the credibility of buyers at Bimura Residence. This research method uses a qualitative descriptive approach. The data of this research uses primary and secondary data. The data collection method used interviews with housing developers, managers, then confirmed with all staff at Bimura Residence and carried out observations. The results of this study are the rebranding efforts carried out by PT. CIP in housing becomes the basis of subsidies through 4 stages of the rebranding effort itself. And what kind of rebranding efforts are the basis of these subsidies in increasing buyer credibility, as well as rebranding services to consumers at Bimura Residence which are supported by supporting factors in increasing buyer credibility at Bimura Residence.